Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1152/ajpcell.00186.2007
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB-dependent transcriptional regulation of the cardiac scn5a sodium channel by angiotensin II

Abstract: (ANG II) increases oxidative stress and is associated with increased risk of sudden cardiac death. The cardiac Na ϩ channel promoter contains elements that confer redox sensitivity. We tested the hypothesis that ANG IImediated oxidative stress may modulate Na ϩ channel current through altering channel transcription. In H9c2 myocytes treated for 48 h with ANG II (100 nmol/l) or H2O2 (10 mol/l) showed delayed macroscopic inactivation, increased late current, and 59.6% and 53.8% reductions in Na ϩ current, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
86
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 51 publications
7
86
0
1
Order By: Relevance
“…Through associated oxidative stress and unfavorable hemodynamic, metabolic, and cytokine influences, MetS leads to development of atrial fibrosis and slow conduction that can be visualized in LA voltage maps as areas of fractionated and low voltage potentials. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Our study demonstrated that advanced electric remodeling and the presence of nonpulmonary vein substrate for AF must be expected in MetS and that the presence and extent of LA low voltage areas were associated with more AF recurrences, a finding supported by a previous study. 32 We suggest that in addition to PVI, extensive ablation to modify these low voltage areas may be necessary to achieve better long-term outcomes in patients with MetS.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Through associated oxidative stress and unfavorable hemodynamic, metabolic, and cytokine influences, MetS leads to development of atrial fibrosis and slow conduction that can be visualized in LA voltage maps as areas of fractionated and low voltage potentials. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Our study demonstrated that advanced electric remodeling and the presence of nonpulmonary vein substrate for AF must be expected in MetS and that the presence and extent of LA low voltage areas were associated with more AF recurrences, a finding supported by a previous study. 32 We suggest that in addition to PVI, extensive ablation to modify these low voltage areas may be necessary to achieve better long-term outcomes in patients with MetS.…”
Section: Discussionsupporting
confidence: 89%
“…[1][2][3][4][5] Renin-angiotensin system and oxidative stress can change the membrane ion channels and modulate the connexin surface expression, leading to slow atrial conduction. [6][7][8][9][10][11][12] This process called electroanatomic remodeling is frequently observed in patients with atrial fibrillation (AF). 13 Increased collagen deposition and matrix volume expansion has been found to correlate with the presence of AF and its persistence.…”
mentioning
confidence: 99%
“…To reveal the functional role of Nav1.7 channel expression in IDC, we demonstrated that expression of the Nav1.7 channel in (38,39). Furthermore, they are also implicated as key regulators of intracellular pH and cell migration (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al [49] found that Kv4.3 channel mRNA was destabilized by angiotensin II-or stretch-activated NADPH oxidase in neonatal rat ventricular myocytes, while Tsai et al [50] reported that expression of the L-type channel alpha1c subunit was increased by angiotensin II through a protein kinase C/NADPH oxidase pathway in HL-1 cells. In H9c2 myocytes or freshly isolated myocytes, angiotensin II decreased Na+ channel (scn5a) mRNA abundance via NADPH oxidase and NF-κB activation [51]. All the above angiotensin II-induced effects are likely to involve Nox2 oxidase activation.…”
Section: Effects Of Nadph Oxidase On Calcium Signalingmentioning
confidence: 99%